2018
DOI: 10.1126/science.aat3188
|View full text |Cite
|
Sign up to set email alerts
|

Ancient genomes document multiple waves of migration in Southeast Asian prehistory

Abstract: Southeast Asia is home to rich human genetic and linguistic diversity, but the details of past population movements in the region are not well known. Here, we report genome-wide ancient DNA data from 18 Southeast Asian individuals spanning from the Neolithic period through the Iron Age (4100 to 1700 years ago). Early farmers from Man Bac in Vietnam exhibit a mixture of East Asian (southern Chinese agriculturalist) and deeply diverged eastern Eurasian (hunter-gatherer) ancestry characteristic of Austroasiatic s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
288
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(327 citation statements)
references
References 63 publications
20
288
1
Order By: Relevance
“…Another hypothesis suggests additional later southward expansion of EA populations. Current studies of SEA ancient human genomes indicated that both Hòabìnhian hunter‐gatherers first recognized about 44 ka years ago and southward expansion of EA farmers about 4,000 years ago influenced the diversity of present‐day SEA populations (Lipson et al, ; McColl et al, ). The findings agree with our ancestral population analyses that the present‐day SEA populations were mainly derived from the SEA ancestries and partly from the EA ancestries.…”
Section: Resultsmentioning
confidence: 99%
“…Another hypothesis suggests additional later southward expansion of EA populations. Current studies of SEA ancient human genomes indicated that both Hòabìnhian hunter‐gatherers first recognized about 44 ka years ago and southward expansion of EA farmers about 4,000 years ago influenced the diversity of present‐day SEA populations (Lipson et al, ; McColl et al, ). The findings agree with our ancestral population analyses that the present‐day SEA populations were mainly derived from the SEA ancestries and partly from the EA ancestries.…”
Section: Resultsmentioning
confidence: 99%
“…Hominin fossils in MSEA are restricted to heavily worn teeth or bone fragments, predominantly found in cave breccias or other sediments with uncertain depositional histories or equivocal chronologies. Recent fossil discoveries have pushed back the projected arrival of anatomically modern humans (AMH) in the region into Marine Isotope Stage (MIS) 4, 57 thousand years ago (ka) or earlier (Demeter et al, ; Rabett, ; Shackelford et al, ; Westaway et al, ), while morphological and genetic studies of fossil and modern populations hint at a complex history of interactions between diverse hominin species, including successive waves of modern humans (Bae, Douka, & Petraglia, ; Corny et al, ; Lipson et al, ; Liu et al, ; McColl et al, ; Sikora, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent fossil discoveries have pushed back the projected arrival of anatomically modern humans (AMH) in the region into Marine Isotope Stage (MIS) 4, 57 thousand years ago (ka) or earlier Rabett, 2018;Shackelford et al, 2018;Westaway et al, 2017), while morphological and genetic studies of fossil and modern populations hint at a complex history of interactions between diverse hominin species, including successive waves of modern humans (Bae, Douka, & Petraglia, 2017;Corny et al, 2017;Lipson et al, 2018;Liu et al, 2015;McColl et al, 2018;Sikora, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the applicability of the DNA Signature Prep Kit had been evaluated and verified on challenging samples, DNA mixture, degradative DNA [48][49][50], formalin-fixed paraffin-embedded tissues [49,51], and remains of skeletons and bones [48,[52][53][54], to extend the applications for forensic sciences [55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Hence, on the basis of the sufficient validations of the stability and homogeneity, more essential data of worldwide populations are needed urgently at present to improve the standard experimental procedures, promote the efficiencies of MPS-based system, and strengthen and unify the contacts between capillary electrophoresis-based (CE-based) and MPS-based data for the basic and extended applications of forensic sciences and others.As the aborigines in Hainan island where was the entrances to East Asia (either the southern entrance from Indo-China peninsula or the northern entrance from Central Asia) [12,[69][70][71], Hainan Li, the second largest population after Han Chinese in Hainan island, has unique ethnic properties and derived characteristics which serves as potential "transfer station" or "bridge" for the Austroasiatic populations (or the Tai-Kadai populations) expansion into East Asia [72][73][74][75]. Therefore, we collected the first batch of DNA polymorphic profiles of the Hlai language-speaking population utilizing the MPS-based ForenSeq™ DNA Signature Prep Kit (DPMA), and multiple population genetic analyses were conducted from different geographic scales incorporation with…”
mentioning
confidence: 99%
“…As the aborigines in Hainan island where was the entrances to East Asia (either the southern entrance from Indo-China peninsula or the northern entrance from Central Asia) [12,[69][70][71], Hainan Li, the second largest population after Han Chinese in Hainan island, has unique ethnic properties and derived characteristics which serves as potential "transfer station" or "bridge" for the Austroasiatic populations (or the Tai-Kadai populations) expansion into East Asia [72][73][74][75]. Therefore, we collected the first batch of DNA polymorphic profiles of the Hlai language-speaking population utilizing the MPS-based ForenSeq™ DNA Signature Prep Kit (DPMA), and multiple population genetic analyses were conducted from different geographic scales incorporation with…”
mentioning
confidence: 99%